Pengelolaan Angkutan Lingkungan (Angling) dalam Perspektif Fungsi-Fungsi Manajemen sebagai Upaya Pemenuhan Pelayanan Transportasi Darat di Kabupaten Tuban - Maskur, Ali; Putri , Idhamaningati; Mohammad , Nuh (Jurnal Ilmiah Administrasi Publik, 2022)
This study aims to describe and analyze the management of Angkutan Lingkungan (Angling) carried out by BUMD PT Ronggolawe Sukses Mandiri Tuban Regency. The results of the study indicate that the management carried out is quite good. This is because in managing Angling has implemented management functions namely planning, organizing, actuating, and controlling (POAC). The driving factors for managing Angling are being able to accommodate more than one person, operating 24 hours, avoiding heat and rain, flexible, iconic, being able to become transportation for persons with disabilities, having the potential to become tourism transportation. While the inhibiting factors are the limited personnel they have, the ordering method is not yet effective, the location of the base is not strategic, the lack of synergy with the Service, and the existence of other online public transportation in Tuban Regency. Theoretically, the research implication is to confirm that Angling management has implemented the management function of POAC, and in practice, it is a consideration for improving existing regulations.